The enhancement of reconsolidation with a naturalistic mild stressor improves the expression of a declarative memory in humans - Coccoz, Veronica (2011)
The reconsolidation hypothesis proposes that a previously consolidated memory recalled by a reminder enters an unstable state (memory labilization) during which it is transiently sensitive to disruption. Although this process has been shown in very diverse species and types of memories, including human declarative memory, elucidating the role of this process is still an open challenge. The hypothesis that reconsolidation allows the incorporation of new information has recently been demonstrated in humans. However, the findings show that, during the reconsolidation phase, memory retention can be increased by pharmacological modulation or real life events in animals have not been found in humans yet. In order to evaluate this, we used a paradigm of human declarative memory whose reminder structure allows us to differentiate between a retrieved labile memory state and a retrieved but non-labile state. Volunteers learned an association between five cue-syllables and their respective response-syllables. 6 days later, the paired-associate memory was reactivated by exposing the subjects to the reminder, and then they received a mild stressor, cold pressor stress (CPS). Poor memory performance was found at both the time of memory reactivation (day 6 after training) and at testing of all groups that were designed as controls (day 7). Conversely, robust memory performance was shown at testing when the CPS administration was concurrent with the retrieved-labile memory state. Results from the present study reveal that a naturalistic mild stressor can enhance reconsolidation, improving the long-term expression of this declarative memory. This finding might have significant implications for the comprehension of memory persistence and memory expression, and add new evidence in order to understand the adaptive meaning of the reconsolidation process.